PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPAS MATERI SIKLUS HIDUP HEWAN PADA SISWA KELAS III SDN WEGOKNATAR - Elsari Jagong, Alvia; Bera, Lukas; Kristiani Maria, Sonya (Jurnal Biogenerasi, 2024)
This study aims to determine the effect of the use of audio-visual media on the learning outcomes of science and science of animal life cycle material in grade III students of SDN Wegoknatar. This type of research is quantitative pre-experimental using a one-group pretest-posttest design. It is carried out on one group without a control or comparison group. The data collection techniques used are test questions, observation sheets and documentation. The sample used in this study was 12 third grade students of SDN Wegoknatar. The data analysis techniques used in this study are normality test, pretest-posttest data, and hypothesis test. From each of the results obtained, it was shown that there was an influence of the use of audio-visual media on the learning outcomes of science science and animal life cycle material in grade III students of SDN Wegoknatar by obtaining an average score of student pretest = 43, 84 and in the posttest = 70.76 This means that there was an increase in student teaching success after using learning video media. Based on the output table of the t-test results, a significance value of 0.001 < 0.05 was obtained, which means that H0 was rejected and H1 was accepted. Thus, it is feasible to state that there is an influence of the use of audio visual media on the learning outcomes of grade III students of SDN Wegoknatar.